Community knowledge and practices regarding antibiotic use in rural Mozambique: where is the starting point for prevention of antibiotic resistance? - Olga Cambaco; Yara Alonso Menendez; John Kinsman; Betuel Sigaúque; Heiman Wertheim; Nga Do; Margaret Gyapong; Johannes John-Langba; Esperança Sevene; Khátia Munguambe (BMC, 2020)
Abstract Background Antibiotic misuse and other types of unnecessary use of antibiotics can contribute to accelerate the process of antibiotic resistance, which is considered a global concern, mostly affecting low-and middle-income countries (LMICs). In Mozambique there is limited evidence on community knowledge and practices regarding antibiotics and antibiotic resistance. As part of the ABACUS project, this paper describes knowledge and practices of antibiotic use among the general population in the semi-rural district of Manhiça to inform evidence-based communication intervention strategies for safer antibiotic use. Methods The study was conducted in Manhiça, a semi-rural district of Southern Mozambique. Sixteen in-depth interviews and four focus group discussions (FGDs) were conducted with community members to explore lay knowledge and practices regarding antibiotics and awareness of antibiotic resistance. The qualitative data was analysed using a combination of content and thematic analysis. The SRQR guidelines for reporting qualitative studies was performed. Results Although participants did not hold any consistent knowledge of antibiotics, their visual recognition of amoxicillin (distinct red yellow capsule) was acceptable, but less so for different types and brands of antibiotics. The majority of participants were aware of the term 'antibiotic', yet the definition they gave was rarely backed by biomedical knowledge. Participants associated antibiotics with certain colours, shapes and health conditions. Participants reported common habits that may contribute to resistance: not buying the full course, self-medication, sharing medicines and interruption of treatment. Most had never heard of the term 'antibiotic resistance' but were familiar with the phenomenon. They often understood the term 'resistance' as treatment failure and likened 'resistance' to non-compliance, ineffective medication, disease resistance or to an inability of the physical body to respond to it. Conclusion There is a broad understanding of the importance of medication compliance but not specifically of antibiotic resistance. In addition, there is a recognized gap between knowledge of responsible drug compliance and actual behaviour. Future qualitative research is required to further explore what determines this behaviour. The existing ability to visually identify amoxicillin by its distinct red and yellow appearance is informative for future awareness and behavioural change campaigns that may incorporate visual aids of antibiotics.